Nonparticipation in adult education programs: Views of blue-collar male workers with low-literacy skills - Deryl Davis-Harrison (Adult Education Research Conference, 1996)
Findings suggest that although low-literate, blue-collar male workers lack confidence in their "book learning" abilities, they are able to maintain their self-concepts by developing a high level of confidence in their work abilities. The resulting high "work esteem" and low "academic esteem" variables, conjointly persist as important determinants of nonparticipatory behavior in organized adult education programs.